The Effect of the Aeration System on Fish Health Performance in Aquaponics - Darmawan, Mochamad Reza; Andriani, Yuli; Subhan, Ujang; Zidni, Irfan (Journal of Fish Health, 2025)
Dissolved oxygen in aquaculture systems, including aquaponics systems, cannot be filled only by natural diffusion, so an artificial aeration system is needed. Suboptimal aeration levels not only affect metabolic activity, but also affect serum and fish blood performance (hematology). This study aims to evaluate the impact of the aeration system on the health and well-being of fish cultivated in an aquaponics system. The method used is by studying the literature related to the aeration system of fish farming carried out in the aquaponic system which is relevant to the keywords of aquaponic system, aeration system, fish health and hematology from various sources such as: Google Scholar, Elsevier, Springer and Research Gate. Based on the comparison of several studies, it can be concluded that the aquaponic system using an aeration system can improve fish health performance based on hematological parameters.